2003
DOI: 10.1253/circj.67.646
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Fulminant Viral Myocarditis With a Short Clinical Course

Abstract: A 75-year-old man recovered from an episode of acute influenza. A myocarditis with a normalized level of serum cardiac troponin T, but less than 2 weeks after recovery, he rapidly fell into cardiogenic shock and died of fulminant myocarditis. The autopsied heart showed marked inflammatory cell infiltration that mainly consisted of mononuclear cells positive for CD8, suggesting that the second bout of myocarditis was caused by viral re-infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…Takehana et al reported that a 75-year-old man who recovered from myocarditis associated with influenza A developed cardiogenic shock and died of fulminant myocarditis. 23 Most patients who survived recovered without any cardiac sequelae in this study, quite similar to previous reports. The degree of myocarditis associated with the 2009 influenza A (H1N1) pandemic was in the present study relatively mild even in patients with fulminant myocarditis.…”
Section: Influenza a (H1n1) 2009 Myocarditis In Japansupporting
confidence: 92%
“…Takehana et al reported that a 75-year-old man who recovered from myocarditis associated with influenza A developed cardiogenic shock and died of fulminant myocarditis. 23 Most patients who survived recovered without any cardiac sequelae in this study, quite similar to previous reports. The degree of myocarditis associated with the 2009 influenza A (H1N1) pandemic was in the present study relatively mild even in patients with fulminant myocarditis.…”
Section: Influenza a (H1n1) 2009 Myocarditis In Japansupporting
confidence: 92%
“…Additionally, recurrent myocarditis in the setting of influenza infection has been reported in 2 cases. One patient had two prior episodes of myocarditis and then a third elicited in the setting of influenza infection, consistent with influenza infection exacerbating an underlying condition . Another patient had resolution of his influenza‐associated myocarditis followed by recurrent myocarditis 22 days after initial presentation …”
Section: Resultsmentioning
confidence: 97%
“…There have been approximately 44 cases of influenza‐associated myocarditis in adult patients described in case reports and case series (Table ) . Among those reported, 52% (23/44) occurred in men and 68% (30/44) occurred in patients under 40 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…The causal agent was not found, but the events occurred following episodes of gastroenteritis or upper respiratory tract infection [5]. Other cases have been reported after streptococcal pneumonia vaccine [12], after a bout of the flu [4], or concomitant to Coxsackie's virus infection [13]. In the case presented above, GAS infection, as proven by a throat swab at the time of the pharyngeal infection, is suggested to be the trigger for the subsequent myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, acute postinfectious myocarditis is principally a monophasic inflammatory disorder. Cases of repetitive or recurrent myocardial inflammation after an initial episode of myocarditis, although reported, are extremely rare and usually occur shortly (weeks to months) following recovery from the first episode [4, 5]. No description of GAS-related nonrheumatic myocarditis recurrence has yet been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%